A high-voltage GaN quasi-vertical metal–insulator–semiconductor Schottky barrier diode on Si with excellent temperature characteristics. (30th June 2022) - Song, Xiufeng; Sun, Baorui; Zhang, Jincheng; Zhao, Shenglei; Bian, Zhaoke; Liu, Shuang; Zhou, Hong; Liu, Zhihong; Hao, Yue
Abstract: In this work, a GaN quasi-vertical metal–insulator–semiconductor Schottky barrier diode (MIS SBD) on Si is demonstrated for the first time. A 4.2 nm thick SiN dielectric is adopted to suppress the reverse leakage. Both the thermionic emission current and the tunneling current under reverse bias are reduced by the SiN interlayer. As a result, the leakage of the MIS SBD is effectively reduced by more than two orders of magnitude and the breakdown voltage (BV) is improved from 121 V for a conventional SBD to 288 V for the MIS SBD. The temperature-dependent reverse I – V characteristics show high-temperature stability of the MIS SBD and the leakage maintains a very low level even at a high temperature of 400 K. In addition, the interface state density is extracted using the conductance method. The quasi-vertical MIS SBD structure exhibits an enhanced BV and excellent temperature characteristics, which indicate that this technique holds great promise for future high-power and high-temperature applications.